Developing broad-spectrum resistance in cassava against viruses causing the cassava mosaic and the cassava brown streak diseases - Sheat, Samar; Winter, Stephan (Frontiers in Plant Science, 2023)
Growing cassava in Africa requires resistance against the viruses causing cassava mosaic disease (CMD) and the viruses causing cassava brown streak disease (CBSD). A dominant CMD2 resistance gene from a West African cassava landrace provides strong resistance against the cassava mosaic viruses however resistance against cassava brown streak viruses is limited to cassava varieties that show tolerance to the disease. The recently identified cassava germplasm that cannot be infected with cassava brown streak viruses provides the new sources of resistance required to protect cassava from CBSD. We present a synopsis of the status of virus resistance in cassava and report about the research to combine resistance against CBSD and CMD. We improve the lengthy and erratic screening for CBSD resistance by proposing a virus infection and screening protocol for the viruses causing CBSD and CMD which allows a rapid and precise assessment of cassava resistance under controlled conditions. Using this approach, we classified virus responses of cassava lines from Africa and South America and identified truly virus-resistant clones that even under the most stringent virus infections cannot be infected with any of the known viruses causing CBSD. A modification of this protocol was used to test seedlings from cassava crosses for resistance against both diseases and broad-spectrum resistance was identified in a workflow that lasted 9 months, from seed germination to identification of virus resistance. The workflow we propose dramatically reduces the evaluation and selection time required in a classical breeding workflow to reach the advanced field trial stage by conducting selection for virus resistance and plant multiplication in parallel. It does not bypass field evaluations; however, cassava resistance assessment in the laboratory limits the later field evaluation to candidates with virus resistance that is defined as: absence of symptoms and absence of virus. The transfer of our virus screening workflow to cassava breeding programs will enhance the efficiency by which resistance against viruses can be selected. It provides a precise definition of the plant (resistance) response and can be used as a model system to tackle resistance in cassava against other diseases.